Leadership Competences as Part of the Competence of a Vocational Education Teacher - Bakatanova , V.; Bulynin , V. (Problems of Engineer-Pedagogical Education, 2023)
The article reveals the properties of leadership and leadership qualities, considers the terms “leadership” and “leadership competence”, provides the passport of leadership competences of a vocational training teacher developed on the basis of state standard 015 specialty (Vocational Education) of the first and second levels of higher education. K.K. Platonov on the structure of human personality and N.V. Kuzmina on the pedagogical system, a matrix of personal qualities of a leader was developed and presented. In the second half of the twentieth century, business leaders faced the problem that employees started attaching less importance to financial incentives for their work. Since then, personnel management techniques have increasingly been relying on the corporate culture and psychological climate in teams, which all depend on the presence of leaders in them. Leaders are able to influence people and organize their work around themselves without resorting to administrative management methods. In this regard, leadership is relevant and important to study and develop for a number of sciences, including pedagogy, psychology, theory and practice of management, sociology, political science, history and behavioral economics. Nowadays, systems and methods of human resource management are becoming increasingly important, with a special place among belonging to leadership competence. It is the vocational education teacher who prepares the working potential of the country, on which the well-being and economic power of our nation depend. That is why special requirements apply to graduates of engineering and pedagogical specialties, because the vocational education teacher is the organizer of both the production and training processes. It is impossible to effectively carry out this organizational function and be a good example to follow without the ability to be a leader who is able to clearly set goals for themselves and others they are responsible for. Prospects for further research in this area concern the opportunity to improve the training of future teachers of vocational education through honing their leadership skills.